Assistance in Obtaining a Business Identification Number (NIB) for Gayam Chips MSMEs to Support Business Sustainability - Mochamad Usman Sufi; Melandri Muchamad Hadi Renata; Nuria Alfina; Angela Nayya Azzahra; Nafia Ilhama (Yayasan Cendekiawan Digital Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) still face challenges regarding business legality, particularly in understanding digital licensing procedures. This situation is also experienced by gayam chips entrepreneurs who have potential local products but do not yet have a formal business identity. This community service activity aims to assist MSMEs in obtaining a Business Identification Number (NIB) through the Online Single Submission (OSS) system. The program was implemented using a participatory approach, involving 12 participants: business owners, members of production families, and production support staff. Assistance was provided through technical guidance, hands-on practice, and reflective discussions related to production and marketing strategies. The results of the activity showed an increase in participants' understanding of the importance of business legality, and that most participants completed the NIB registration process. Furthermore, this activity also revealed the potential of gayam chips as a traditional food product with unique value and a simple marketing strategy that remains effective despite limited seasonal raw materials. Business legal assistance has proven to be the first step in strengthening MSMEs' capacity and encouraging the sustainability of businesses based on local potential.